2018
DOI: 10.1002/aur.1949
|View full text |Cite
|
Sign up to set email alerts
|

Chinese children with autism: A multiple chemical elements profile in erythrocytes

Abstract: It is suggested that abnormal levels of some chemical elements may contribute to the development of autism spectrum disorders (ASD). In this work, the impact of element imbalances on the risk and severity of ASD was investigated, focusing on the analysis of abnormal levels of the multi-chemical elements profile in erythrocytes compared with typically developing children. Furthermore, the results showed a significant correlation between abnormal levels of several chemical elements and the severity of the autist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…However, under physiological conditions, PGE 2 is a signaling molecule that plays an important role in brain development, regulating proliferation and differentiation of neuroectodermal stem cells by affecting the Wnt/β-catenin pathway and is thus significant for the expression of genes important for brain development [57]. It is postulated that this is the mechanism behind the role of PGE 2 in neurodevelopmental diseases, for example in ASD [57], which could explain the increased risk of this disorder in children with elevated blood Pb levels [23][24][25][26].…”
Section: Prostanoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, under physiological conditions, PGE 2 is a signaling molecule that plays an important role in brain development, regulating proliferation and differentiation of neuroectodermal stem cells by affecting the Wnt/β-catenin pathway and is thus significant for the expression of genes important for brain development [57]. It is postulated that this is the mechanism behind the role of PGE 2 in neurodevelopmental diseases, for example in ASD [57], which could explain the increased risk of this disorder in children with elevated blood Pb levels [23][24][25][26].…”
Section: Prostanoidsmentioning
confidence: 99%
“…It is linked to numerous metabolic and structural changes in the developing brain (for detailed review see [12][13][14][15]), resulting in various cognitive disorders [16][17][18][19]. Children exposed to Pb in the early stages of development show a high incidence of many neurodevelopmental diseases, such as hyperactivity, emotional symptoms and conduct disorder [20], attention-deficit hyperactivity disorder (ADHD) [21,22], autism spectrum disorder (ASD) [23][24][25][26], and tend to have lower IQs [27,28]. Until recently, the safe blood Pb concentration was believed to be 10 µg/dL [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the ASD group showed lower Zn concentrations in 16 studies (31%), and higher Zn concentrations in 10 studies (19%), compared to the control group. Of the total number of included studies, Sweetman et al (2019), Wu et al (2018), and Gentile et al (1983) did not report differences in Zn concentrations between the groups [ 17 , 34 , 45 ]. Of these, Sweetman et al (2019) reported that Zn levels exceeded the limits for reference values, where 38 children (26%) had Zn levels < 10.7 μmol/L (17 in the ASD group [23%] and 21 in the control group [29.2%]) [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Metal/elemental disturbances have been associated with NDDs [98], suggesting a role of metal dyshomeostasis in their etiology, albeit with much of the focus of studies on NDDs on peripheral markers rather than the brain. For example, alterations in the levels of metals and/or trace metals in serum or in hair or nails are reported and sometimes correlate with the features or severity of ASD [99][100][101][102][103][104][105][106][107]; the observed metal profiles can differ by sex [108] and geographic location. Alterations in the brain metal levels in ASD have been reported [109,110], as have correlations of trace metal levels with neuroinflammatory markers [111].…”
Section: Evidence For the Involvement Of Metals In Ndds And Ndgdsmentioning
confidence: 99%